Effects of biofeedback training on HRV, mood state and shooting performance of shooters - Donghai, Huang; Muhammad Nubli, Abdul Wahab (e-International Publishing House, 2024)
This study investigates the effects of biofeedback training on the HRV, emotional state, and shooting performance of athletes. Results indicate significant improvement in athletes' HRV frequency domain indices (p < 0.05), reduced negative emotions like tension and anger (p < 0.05), increased vitality and positivity, though changes in fatigue and self-emotional state weren't statistically significant (p > 0.05). Shooting performance significantly improved post-training (p < 0.01). This suggests that biofeedback training positively impacts autonomic nervous system function, emotional stability, and shooting skills. Biofeedback training significantly enhances shooting performance by improving HRV, optimizing emotional state, and strengthening emotional regulation abilities.